Unveiling exogenous gaps enabling a cluster organization’s internationalization process - Aihie Osarenkhoe; Daniella Fjellström; Mabel Birungi Komunda (Central European Management Journal)
Purpose – We examined the internationalization process of business promotion organizations. We focused on the key stages and strategies and how the networks formed during this process can support their partners, particularly SMEs, in facilitating international expansion. Design/methodology/approach – The theoretical lens: We combined the experiential learning-commitment interplay of the Uppsala model with a similar mechanism focused on business network relationships. A qualitative methodology: We used it to explore the question and the various forms of embeddedness within networks, offering an in-depth examination, particularly in the challenging natural settings of a cluster organization in geographic information systems (GIS). Findings – We found that the cluster organization’s internationalization began regionally, forging connections with clusters in the Nordic and Baltic countries and Europe. Over time, the cluster recognized the importance of innovation leadership, leading to the integration of its core competencies with complementary technologies from other global geospatial technology hubs. Research limitations/implications – The study fills research gaps by examining global linkages between regional clusters and international partners, focusing on external gaps. We explored how clusters can leverage global innovation systems and networks for matchmaking, capitalization and investment. Moreover, we addressed the need for more research on cross-cluster gaps and barriers to global market interaction. By providing insights into expanding beyond local interactions, the study enhances understanding of how clusters can increase the global reach and competitiveness of firms within them. Originality/value – The platform established during the internationalization process was crucial, as SMEs within clusters often lack the resources, time and expertise to enter international markets alone. This platform helps SMEs overcome barriers such as size, resources and unfamiliarity with foreign markets.